Training in regenerative agriculture as a prioritized capacity building need in Caquetá, Colombia - Jimenez, Maria de los Angeles; Benitez, Diego; Rodriguez, Gregorio; Rodriguez, Luz A.; Vanegas Cubillos, Martha (2025)
This document presents the methodology used to train the community of rural producers associated with Agrosolidaria La Montañita in understanding and applying the principles of regenerative agriculture from a practical perspective. The objective was for participants to learn how to read the soil, plants, and local biology in order to design a biological transition plan tailored to the specific conditions of their territory.